Técnicas básicas para el estudio de los moluscos - Monge-Nájera, Julián (2003)
This chapter overviews the basic techniques for statistical analysis, molecular study, photography and illustration in malacological research. A guide of how to select the appropriate statistical tests, with malacological examples, as well as digital photography, are included together with selected references.